Erratum. Issue 1 (August 2014) - Unknown
Diniz, R. C. R., Martins-Costa, H. C., Machado, S. C., Lima, F. V., & Chagas, M. H. (2014) Repetition duration influences ratings of perceived exertion. Perceptual & Motor Skills: Physical Development & Measurement, 118, 1, 261–273. DOI: 10.2466/03.06.PMS.118k11w6 The authors wish to correct Footnote 2 on page 261 to read: 2 The authors thank André Gustavo Pereira de Andrade, Ph.D., for assistance in the statistical analysis of this study and FAPEMIG (Fundação de Amparo à Pesquisa do Estado de Minas Gerais) for assistance with financial resources for the research.